Key Issues of Determining the Scope of Subjects on the Civil Procedural Structure of Securing a Claim in the RA - Hovhannisyan, Vahe (Bulletin of Yerevan University C: Jurisprudence, 2022)
In the article, the author considers and analyzes the issues of determining the scope of subjects of securing a claim, as a result of which the peculiarities of realization of the judicial status, subjective rights and legal interests of the applicants for securing measures, are presented. It is emphasized that in order to correctly define the scope of the subjects entitled to apply for taking measures to secure the claim, basically, it is necessary to reconsider the purpose of execution of this institution, considering it as the procedural mechanism which can reasonably exclude possible losses and tend to realize the material legal relations established by a judicial act which has entered into legal force, since the obligation of its guarantee and responsibility lies with the country. The subjects interested in the execution of the final judicial act should have the opportunity to submit claim security measures, the scope of which should include the participants of the judicial proceedings with their distinctive interests. On top of that, the article argues that in the context of securing a claim, it is necessary to regulate the protection of the rights and legitimate interests of others, which should be ensured, if the right to apply for replacement, transformation or revocation of a security or the right to claim compensation of possible losses will be provided for those persons against whom such measures have been taken or whose rights and obligations are affected by the undertaken measures.
Keywords: securing a claim; measures to secure a claim; bilateral claim; countering security; court initiative, respondent; respondent; protection of the rights of others